Project takes action for climate-responsive agriculture policies in East Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
The Policy Action for Climate Change Adaptation (PACCA) project is led by the International Institute of Tropical Agriculture (IITA) as part of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) Flagship on Policies and Institutions for Climate-Resilient Food Systems. The four-year project seeks to inform and link policies and institutions from national to local level for the development and adoption of climate resilient food systems in Uganda and Tanzania. This is done through connecting the scientific community with policy actors through Learning Alliances to generate knowledge exchange and engagement. In this video, Edidah Ampaire talks about the PACCA project, how the team works, with whom and some of the main encountered challenges so far. Video by Elisabeth van de Grift, CCAFS and editing by Cecilia Schubert, CCAFS.